Pengembangan Pusat Konseling Mahasiswa Unsoed Melalui Pendidikan Dan Pelatihan Mahasiswa Sebagai Peer Counselor - Triyanto, Endang; Rahayu, Eva; Puspita, Dyah Retna (Jurnal Keperawatan Soedirman, 2013)
Students problem are learning barriers, lack of self-motivation, time management, adaptation difficulties, not confident, and promiscuity. Students who are troubled often cover themselves with faculty and their families. They would rather confide in with their peers. The Student Counseling Center is newly formed and should be developed through education and training to improve the knowledge, skills and attitudes as a peer counselor. Activities carried out to 10 student peer counselor at the campus of the Faculty of Medicine Nursing and Health Sciences on 3-5 September 2013. There is a growing knowledge about adolescent growth and development end, a variety of student issues and solutions by 80%. Trainee is able to demonstrate the correct procedure counseling. Dissemination to other students conducted using online media. Students can use to get solutions of problems.